Silica Phosphoric Acid as an Efficient Heterogeneous Catalyst for Protection of Carbonyl Groups Under Solvent Free Conditions - BADRI, RASHID; REZA KIASAT, ALI; KESHAVARZ, MOSADEGH (Asian Journal of Chemistry, 2010)
Aldehydes and ketones were protected by phenyl hydrazine and 2,4-dinitrophenylhydrazine in the presence of silica phosphoric acid in short time and high yields.